1995
DOI: 10.1182/blood.v85.12.3688.bloodjournal85123688
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic profile of minimally differentiated (FAB M0) acute myeloid leukemia: correlation with clinicobiologic findings [see comments]

Abstract: Cytogenetic data were studied in 26 patients with de novo acute myeloid leukemia (AML) with minimal myeloid differentiation, corresponding to the M0 subtype of the French-American-British classification, in correlation with cytoimmunologic and clinical findings. Clonal abnormalities were detected in 21 cases (80.7%), 12 of which had a complex karyotype. Partial or total monosomy 5q and/or 7q was found, either as the sole aberration or in all abnormal metaphases, in 11 patients; in 8 cases, additional chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…The overall incidence of AML-M0 is similar to that in Western countries, which has been reported to be 0.1% to 9%. 3,8,10,11,[16][17][18][19] In this study, we confirmed that AML-M0 is a unique AML subtype, which showed higher incidence of organ infiltration and more frequent expression of CD7 and CD34, as well as complex cytogenetic changes of the leukemic cells than other AML subtypes. Although lg and TCR␤ gene rearrangements had been found in some AML-M0 cases, 8 all 10 patients tested in this study showed germline configuration of both genes, which was feasible to exclude lymphoid differentiation of the leukemic cells in these patients.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The overall incidence of AML-M0 is similar to that in Western countries, which has been reported to be 0.1% to 9%. 3,8,10,11,[16][17][18][19] In this study, we confirmed that AML-M0 is a unique AML subtype, which showed higher incidence of organ infiltration and more frequent expression of CD7 and CD34, as well as complex cytogenetic changes of the leukemic cells than other AML subtypes. Although lg and TCR␤ gene rearrangements had been found in some AML-M0 cases, 8 all 10 patients tested in this study showed germline configuration of both genes, which was feasible to exclude lymphoid differentiation of the leukemic cells in these patients.…”
Section: Discussionsupporting
confidence: 76%
“…Similar findings had been reported from other institutions. 8,11,18 There were no specific chromosomal abnormalities in this subtype of AML. The common aberrations shown in this study as well as from literature, such as +8, −7/7q−, −5/5q−, can also be detected in other hematologic malignancies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This makes assessment of the presence of dysplastic features difficult. Multilineage dysplasia in AML M0, however, has been described (Cuneo et al , 1995; Lemež et al , 1998), which may suggest a stem cell dysfunction in AML M0.…”
Section: Discussionmentioning
confidence: 97%
“…Cohen et al (1998 ) found no distinguishing features of blasts in AML M0; two‐thirds of patients had blasts with cytoplasmic vacuoles, but none had cytoplasmic budding. Trisomy 13 was found in 5/26 patients with AML M0 ( Cuneo et al , 1995 ); 4/34 adults with AML expressing lymphoid markers had +13 or structural aberrations of 13q ( Cuneo et al , 1992), and 2/17 AML M0 patients had +13 and 1/17 had tetrasomy 13 ( Cohen et al , 1998 ). A high proportion of karyotypically normal cells was observed in our patients.…”
Section: Discussionmentioning
confidence: 99%